NTD Health: An electronic medical record system for neglected tropical diseases. - Ochoa, Rodrigo; Álvarez, Alessa; Freitas, Jordan; Purkayastha, Saptarshi; Vélez, Iván D. (Biomédica: Revista del Instituto Nacional de Salud, 2022)
Introduction: The use of technological resources to support processes in health systems has generated robust, interoperable, and dynamic platforms. In the case of institutions working with neglected tropical diseases, there is a need for specific customizations of these diseases. Objectives: To establish a medical record platform specialized in neglected tropical diseases which could facilitate the analysis of treatment evolution in patients, as well as generate more accurate data about various clinical aspects. Materials and methods: A set of requirements to develop state of the art forms, concepts, and functionalities to include neglected tropical diseases were compiled. An OpenMRS distribution (version 2.3) was used as reference to build the platform, following the recommended guidelines and shared-community modules. Results: All the customized information was developed in a platform called NTD Health, which is web-based and can be upgraded and improved by users without technological barriers. Conclusions: The electronic medical record system can become a useful tool for other institutions to improve their health practices as well as the quality of life for neglected tropical disease patients, simplifying the customization of healthcare systems able to interoperate with other platforms.